Durum wheat and local chains: A new strategy to strengthen locally selected genotypes - Carboni G.; Dettori M.; Goddi G.; Mulè P.; Satta B.; Spanu E. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Wheat is the most important crop in many areas of the Mediterranean Region. In Sardinia (Western Mediterranean, Italy), this crop has been grown for a very long time. As a consequence, the Island is rich in traditional breads and pasta completely different from those that can be found in other parts of Italy and the Mediterranean. Hence, a specific regional breeding programme has been developed in Sardinia to meet the different needs of farmers, millers, end-product processors and consumers as well as to strengthen the peculiarities of the Sardinian durum wheat chain. This programme aims to release specific cultivars showing strong genotype × environment interaction (GE) to Sardinian growing conditions. At the moment, two Sardinian varieties have been released in the last years: Karalis and Ampsicora. These varieties have been grown and tested in different areas of the island together with other varieties used as a check and the main agronomic and quality traits have been analysed. Finally, these varieties have been used either in purity or in blends, to make Sardinian traditional breads and pasta. The success of this programme enabled the development of a local durum wheat chain identified by a quality brand called Semenadura.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)